Who were the Beatles? - Edgers, Geoff; Tugeau, Jeremy (New York : Grosset & Dunlap, 2006)
"A biography of the Beatles, the world$1 (Bs most famous rock band"--Provided by publisher.s
Who were the Beatles -- John Lennon -- Paul McCartney -- Ringo Starr -- George Harrison -- Forming the band -- A new name, a new look -- Beatlemania -- Road weary -- The beginning of the end -- Everyone is going solo -- The saddest day.
Includes bibliographical references (p. 104-106).
Keywords: Beatles -- Juvenile literature; Rock music -- England -- History and criticism -- Juvenile literature; Rock music -- England -- History and criticism; Beatles; Musicians -- Biography